2022
DOI: 10.1097/md.0000000000029930
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopy-assisted bone grafting for the treatment of SNAC stage I without radial styloidectomy

Abstract: To report the clinical and radiological outcomes of arthroscopic bone grafting and percutaneous K-wire fixation without radial styloidectomy in patients with scaphoid nonunion advanced collapse (SNAC). We retrospectively analyzed the records of 15 patients with SNAC who were treated with arthroscopic bone grafting and percutaneous K-wire fixation and subsequently followed up for a minimum of 1 year between November 2009 and March 2018. The clinical outcomes were evaluated by comparing the range of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Some studies included patients with stage I SNAC [ 15 , 18 , 19 , 21 ] and radio-carpal or midcarpal osteoarthritis [ 21 ], with imaging suggestive of avascular necrosis [ 21 ]. One author [ 19 ] considered nonunion to be a permanent fracture at 3 months instead of 6 and described revision surgery, SNAC grade II, and avascular necrosis of the proximal pole.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies included patients with stage I SNAC [ 15 , 18 , 19 , 21 ] and radio-carpal or midcarpal osteoarthritis [ 21 ], with imaging suggestive of avascular necrosis [ 21 ]. One author [ 19 ] considered nonunion to be a permanent fracture at 3 months instead of 6 and described revision surgery, SNAC grade II, and avascular necrosis of the proximal pole.…”
Section: Resultsmentioning
confidence: 99%
“…Seven authors performed postoperative CT scans as routine to confirm union, and three used CT to better study doubtful cases [ 15 , 17 , 25 ]. One author did not use CT in any patient to confirm union [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lee and Jung [20] have reported that in 15 SNAC stage I patients, pain in the radial side is improved by only performing sufficient arthroscopic debridement including joint capsule for synovitis and degenerative change around the radial styloid process without performing radial styloidectomy after correcting scaphoid nonunion. Therefore, for non-weight-bearing joints such as wrist in degenerative osteoarthritis patients, arthroscopic synovectomy including debridement is expected to lead to symptom improvement and joint movement increase.…”
Section: Resultsmentioning
confidence: 99%
“…Synovectomy is often an integral part of procedures for treating conditions of degenerative nature amenable for arthroscopic surgery, such as wafer resection for ulnar impaction syndrome (UIS), debridement in scaphoid-trapezium-trapezoid (STT) osteoarthritis, radial styloidectomy for styloid impaction on the scaphoid, scaphoid nonunion advanced collapse (SNAC), and triangular fibrocartilage complex (TFCC) resection for degenerative changes [18][19][20][21][22]. So far, in patients with osteoarthritis, the effect of arthroscopic synovectomy is probably short-term.…”
Section: Indicationsmentioning
confidence: 99%
“…In this system, the interface between the fractured proximal pole of the scaphoid and the radius is not included since it is frequently spared. The Vender classification of SNAC wrist has become the standard system for communication between professionals and researchers (Abdelaziz et al., 2020; Lee and Jung, 2022; Nakamoto et al., 2023).…”
Section: Introductionmentioning
confidence: 99%